Aplicación de un modelo estadístico para evaluar la reactividad alcalina potencial en rocas basálticas - Maiza, Pedro (1998)
Samples of basaltic rocks from differenlocations of Río Negro and Neuquén provinces were studied by means of the the petrographic method (ASTM C-295), the mortar bars method (ASTM C-1260) and the chemical test method (ASTM C-289). Besides, an aliquot of the solution was analyzed by ICP, to determine the contents of Al$latex ^{_{2}} $and MnO. The obtained results were statistically treated by the Principal Components method and compared with the results obtained in a previous work. lt is concluded that expansion is closely related to the dissolved silica contributed by volcanic glass and its alteration products, and by poorly crystallized silica. lts propases a prompt method to establish the reactivity potential using the Principal Components statistical method.